2015
DOI: 10.1177/1933719114565029
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Renin—Angiotensin System Pathways in the Human Decidua

Abstract: Pregnancy outcome is influenced, in part, by the sex of the fetus. Decidual renin messenger RNA (REN) abundance is greater in women carrying a female fetus than a male fetus. Here, we explore whether the sex of the fetus also influences the regulation of decidual RAS expression with a known stimulator of renal renin and cyclic adenosine monophosphate (cAMP). Cyclic adenosine monophosphate had no affect on decidual REN expression, since REN abundance was still greater in decidual explants from women carrying a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…These same processes may also be at play in the decidua. As described above there is a reduced level of expression of the ACE2/Ang‐(1‐7)/MasR pathway in decidua from women with male fetuses . We postulate that this reduction in activity of the RAS anti‐inflammatory pathway makes pregnancies carrying male fetuses more vulnerable to inflammation, so putting them at greater risk of preterm birth.…”
Section: The Pro‐inflammatory and Anti‐inflammatory Roles Of The Decimentioning
confidence: 70%
See 2 more Smart Citations
“…These same processes may also be at play in the decidua. As described above there is a reduced level of expression of the ACE2/Ang‐(1‐7)/MasR pathway in decidua from women with male fetuses . We postulate that this reduction in activity of the RAS anti‐inflammatory pathway makes pregnancies carrying male fetuses more vulnerable to inflammation, so putting them at greater risk of preterm birth.…”
Section: The Pro‐inflammatory and Anti‐inflammatory Roles Of The Decimentioning
confidence: 70%
“…All components of the RAS have been identified in term human decidua, placenta, myometrium, and fetal membranes [22][23][24] and it has been demonstrated that the decidua is the major source of prorenin protein within the human uterus. 25,26 That is, there is a low level of expression of prorenin mRNA (REN) in amnion and chorion, but amnion and chorion, like decidua, contain high levels of prorenin protein. 27,28 The low level of expression of amnion REN mRNA in the presence of very high levels of prorenin protein suggests that prorenin secreted from the decidua diffuses into the fetal membranes.…”
Section: Sex-specific Expression Of the Intrauterine Renin-angiotenmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis is one of the most critical steps in hepatic carcinoma progression [8][9][10]. Recent studies have revealed that the renin-angiotensin system (RAS), which regulates a diversity of physiological functions including blood pressure, fluid balance and placental development [11][12][13], is involved in the regulation of angiogenesis and may have an important role in the progression of hepatic carcinoma [14,15]. Angiotensin (Ang) II is the major biologically active effector generated by the RAS system in vasculature, and increasing evidence has shown that Ang II facilitates cancer cell behavior in various human malignancies through cell proliferation, migration and metastasis.…”
mentioning
confidence: 99%
“…Ang II acts through two different transmembrane receptors in the G protein-coupled receptor family: Ang II type 1 (AT1) and type 2 (AT2) [20]. It has been reported that Ang II stimulates vasoconstriction, aldosterone production, angiogenesis and cell proliferation by the AT1 receptor and produces the opposite effects via the AT2 receptor [12,21,22]. It is well known that the AT1 receptor mediates most of the physiological and pathological functions of Ang II by interacting with various G proteins, producing second messengers and also activating multiple intracellular protein kinases [23].…”
mentioning
confidence: 99%